Beyond borders: Navigating non-traditional security challenges in Central Asia - Chatterjee, Souvik (Universitas Airlangga, 2024)
Since the end of the Cold War, non-traditional security threats have been a significant concern for five post-communist Central Asian powers, namely Kyrgyzstan, Uzbekistan, Tajikistan, Turkmenistan, and Kazakhstan. Security strategy for Central Asian powers remains predominantly entrenched in hard or military-oriented security. However, the contemporary challenges to regional security in Central Asia are related to human security stemming from the growth of transnational criminal groups, illegal immigration, water security, climate change, and others. Determining how non-traditional threats have impacted regional stability in Central Asia is, thus, the primary objective of this research. The descriptive method, a prominent social research method, sheds light on the recurrent pattern and meaning of complex security issues affecting CARs. The data is collected both from primary and secondary sources such as government reports, e-resources, news articles, journal articles, and others, to facilitate a deeper understanding of the different dimensions of security issues. By juxtaposing both data, this article highlights the interlink between traditional and non-traditional security challenges. The findings of this study suggest that Central Asian republics are required to become more resilient to shocks from the inside and avoid state failure. Sustainable development strategies must be embraced by governments with support from major powers such as Russia, China, and the US to lessen the political unrest, violence, and conflicts.